Adjunctive Treatment of Periodontal Defects Using Fibroblast Growth Factor 2: A Review of Case Reports with Long-term Follow-up - Atarbashi-Moghadam, Fazele; Baghani, Zahra; Ghased, Ali (Journal of Dental School, 2025)
Objective(s): Application of fibroblast growth factor 2 (FGF2) as an adjunctive treatment in periodontal regeneration is a treatment modality. Several recent case reports describe the application of FGF-2 in different periodontal defects with detailed information and long-term follow-ups. The aim of this review was to assess the effect of FGF-2 on periodontal regeneration and patient quality of life in cases with long-term follow-up. Methods: An electronic search was performed in PubMed Central, Scopus, and web of science databases from 1990 until December 2023. The search included all case reports in which FGF2 was used for periodontal defect treatment with long-term follow-up. Case series which described detailed data of their cases were also evaluated. Ten articles including 12 patients, 23 teeth, and 25 defects were included in the study. Results: Most of the treated defects were infrabony defects (84%), followed by furcation defects (12%). Probing depth (PD) reduction and clinical attachment loss (CAL) gain were seen in all defects and evidence of bone fill was documented. All cases had a follow-up duration of at least 12 months, with the greatest follow-up time of 9 years. Conclusion: Adjunctive treatment of periodontal defects using FGF-2 is an effective and stable treatment modality that provides patients’ satisfaction. However, more studies in this field are recommended.